Non-Genetic Factors Affecting The Mortality Of Cage-Reared Broiler Rabbits (Oryctologus Cuniculus) Maintained Under Tropical Climatic Conditions Of Tamil Nadu - Kumar, V.Ramesh Saravana; Iniyah, K.; Sivakumar, K.; Thiruvenkadan, A.K.; Singh, D. Anandha Prakash; Ramesh, V.; Muralidharan, J.; Kannan , D. (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
The influence of non-genetic factors namely breed, sex, age, season and cause of death on the mortality of rabbits were studied utilizing a total of 835 mortality records over a period of 20 years. The study revealed that there is a significant difference (P<0.05) in number of pre-weaning mortalities between seasons, with more mortality in summer and least in winter season. The pre weaning mortality observed in Soviet Chinchilla in summer, south-west monsoon, north-west monsoon and winter seasons were 29.53, 28.37, 27.60 and 14.48 per cent, respectively and the values observed in White Giant were 32.80, 27.12, 32.49 and 7.57 per cent, respectively. The post weaning mortality did not differ significantly between breeds, sexes and seasons. The cause of death did not influence the number of mortality between four seasons of the year. However, pneumonia and enteritis resulted in more mortalities than other causes.